Politics, power and poverty in South Asia - Chalam, K.S. (2003)
The first general assembly of the south Asia alliance of poverty eradication (SAAPE), held in Colombo in June, stressed the need to politicise the issue of poverty in the region by building common platforms to share and link each other's experiences, benefit from their plurality, and enable the poor to take the lead in development. - Reproduced.
Keywords: Poverty - South Asia; Poverty